2012
DOI: 10.1016/j.vacuum.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

PECVD coatings for functionalization of point-of-care biosensor surfaces

Abstract: In early stage disease diagnosis, an accurate and reliable measurement of low concentrations of specific biomarkers is a key need. The detection technique requires the reaction of an antibody, which is generally covalently bound to the biosensor platform, with its antigen. The application of Zeonor®, a cyclo olefin copolymer (COP) with very low autofluorescence, good optical properties and high precision molding characteristics, as a biosensor platform has been demonstrated recently. Highly reproducible, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In a further paper from the same research team, the cyclo olefin copolymer was coated with different silanes for biochemical probe immobilization. 189 DPI showed that the number of surface amine groups was nearly 78 . 10 14 cm -2 , and treatment with buffer containing Tween diminished it until to 66 .…”
Section: Polymer Interactionsmentioning
confidence: 99%
“…In a further paper from the same research team, the cyclo olefin copolymer was coated with different silanes for biochemical probe immobilization. 189 DPI showed that the number of surface amine groups was nearly 78 . 10 14 cm -2 , and treatment with buffer containing Tween diminished it until to 66 .…”
Section: Polymer Interactionsmentioning
confidence: 99%
“…85 Consequently, plasma enhanced-CVD (PECVD) has been adopted as a potential CVD technique for surface functionalization of pointof-care (POC) diagnostic platforms. 86 …”
mentioning
confidence: 99%
“…Multiple studies have used PECVD for the deposition of various end-groups such as amines, carboxylic, mercapto, epoxy, and polyethylene glycol to address the problem of nonspecific binding of single-stranded DNA or other proteins of interest. Parameters such as higher RF power lead to increase in thickness of the film due to increased rate of deposition [140,141]. Monomers such as amino silanes, allylamine, and allyl organophosphates have been commonly used for the deposition of thin films with reactive functional groups [58,127].…”
Section: Biosensorsmentioning
confidence: 99%